Pricing ﬂoating strike lookback put option under heston stochastic volatility - Wirtu, Teferi Dereje; Ngare, Philip; Kube, Ananda (International Research Publication House, 2017)
The pricing problems of the exotic options in the ﬁnance do not have the analytic solutions under stochastic volatility and so it is difﬁcult to calculate the option prices or at least it requires much of time to compute them. This study provides the required theoretical framework to practitioners for the option price estimation. This paper focuses on pricing for ﬂoating strike lookback put option and testing option pricing formulas for the Heston stochastic volatility model, which deﬁnes the asset volatility as the stochastic process. Our pricing method is depending on the PDE approach on Heston stochastic volatility model and homotopy analysis method. Heston model has received the most attention then it can give a acceptable explanation of the underlying asset dynamics. The resulting formula is well connected to a Black–Scholes price that is the ﬁrst term of the series expansion, which makes computing the option prices fairly efﬁcient.
Keywords: Lookback put option; Option pricing; Stochastic volatility model; Heston model; Homotopy analysis method.